2023
DOI: 10.3389/fpsyg.2022.1112308
|View full text |Cite
|
Sign up to set email alerts
|

Mediation effects of cognitive, physical, and motivational reserves on cognitive performance in older people

Abstract: IntroductionWe study from a multidimensional perspective the different factors that help prevent the development of cognitive impairment in old aging.MethodsThis study analyzed in 300 elderly subjects the relationship between cognitive reserve (CR), physical reserve (PR) and motivational reserve (MR) with cognitive impairment. This study also takes into consideration different variables (sex, age, educational level, and institutionalization) that might affect the results in the different types of reserves (CR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Indeed, it has been shown that the number of daily steps and the CR total measure explained approximately 18% of the variance in the MMSE condition, as well as 32% of the variance in the MMSE condition was explained by time spent on leisure activities and daily steps. Altogether, these findings extend those of previous studies that highlighted the predictive role of CR on physical reserve (Martinčević & Vranić, 2023) and of CR and physical reserve on healthy cognition in late adulthood (Sanchez Cabaco et al, 2023). Specifically, the significant indirect effect of CR—especially the CRIq-Hobby measure—and daily steps on the MMSE score suggests that the cognitive reserve and physical one contribute in preserving the global cognitive functioning of older individuals who age well.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Indeed, it has been shown that the number of daily steps and the CR total measure explained approximately 18% of the variance in the MMSE condition, as well as 32% of the variance in the MMSE condition was explained by time spent on leisure activities and daily steps. Altogether, these findings extend those of previous studies that highlighted the predictive role of CR on physical reserve (Martinčević & Vranić, 2023) and of CR and physical reserve on healthy cognition in late adulthood (Sanchez Cabaco et al, 2023). Specifically, the significant indirect effect of CR—especially the CRIq-Hobby measure—and daily steps on the MMSE score suggests that the cognitive reserve and physical one contribute in preserving the global cognitive functioning of older individuals who age well.…”
Section: Discussionsupporting
confidence: 90%
“…Extending the above-mentioned outcomes, Cabaco et al, (2023) recently revealed that both self-assessed physical reserve and CR mediate the effect of age and educational attainment on memory efficiency and global cognition of 55-99-year-old individuals. In addition, Martinčević and Vranić (2023) found that a proxy of CR, namely, time spent for leisure activities, contributed to predicting self-reported physical activity in late adulthood.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Additionally, in older adults, PA has been shown to reduce social isolation and improve quality of life [13,14] and cognitive function; it is also associated with positive changes in brain electrical activity [9]. Furthermore, studies have shown that older adults with higher cognitive, physical, and motivational reserves have less cognitive decline [15], and that there is a relationship between PA and cognition [16][17][18].…”
Section: Introductionmentioning
confidence: 99%